Exploring the needs and barriers for death education in China: Getting answers from heart transplant recipients' inner experience of death - Shu, Wan; Miao, QunFang; Feng, JieHui; Liang, GuanMian; Zhang, Jing; Zhang, Jinsheng (Frontiers in Public Health, 2023)
Background Leading to think about death is for better living, how to carry out death education is an important issue for the world to think about. The purpose of the current study was to explore the attitude of heart transplant recipients towards death and their inner real experience in order provide information for development of death education strategies. Methods A phenomenological qualitative study was conducted by snowball method. A total of 11 patients, who had undergone heart transplantation for more than one year, were recruited to the current study for semi-structured interviews. Results Five themes were identified: “Not avoid talking about death”, “Feeling fear about the pain in the process of death”, “Wanting a good death at the end of life”, “The richness of feelings during near-death is surprising”, and “Being close to death makes people more receptive to death”. Conclusion Heart transplant recipients have a positive attitude towards death and wish for “good death” at the end of life. These patients' near-death experiences and positive attitudes towards death during the course of their illness provide some food for thought and a basis for how to implement death education and develop an experiential approach to death education in China.